IMPLEMENTASI PROGRAM PENGEMBANGAN BUDAYA BACA DALAM PENGELOLAAN PERPUSTAKAAN DI KANTOR ARSIP DAN PERPUSTAKAAN DAERAH KABUPATEN SUMEDANG - Noni Daeni (LPPM UNSAP & FISIP UNSAP, 2018)
This study aims to determine, obtain objective data and information regarding the Implementation of the Reading Culture Development Program in the Management of Libraries in the Archives and Regional Library of Sumedang Regency. In this case the researcher traced through the Policy Implementation Model. The method used in the preparation of this report is a qualitative method (naturalistic setting) with descriptive type. Determination of targets is taken by using purposive sampling technique where the object is implementing the policy with certain considerations. Samples used in this study were 5 people namely Head of Administration, Head of Planning, Management, Archive Storage, Head of Research and Development, Head of Planning, Management of Reference services, Functional Position Groups. Data collection techniques through literature study, field studies (Observation, In-depth interviews, Documentation) and Triangulation.While the data processing procedure is carried out by referring to the basic operation of quoting from the Miles and Huberman Model, cited by Sugiono (2005: 91). Based on the results of research and discussion, researchers found that the Implementation of the Reading Culture Development Program in the Management of the Sumedang District Library was still quite low. This can be seen from several obstacles. Obstacles to the Implementation of the Reading Culture Development Program in Library Management in the Sumedang District Archives and Library Offices are as follows: lack of public awareness about the importance of reading culture, conditions of facilities and infrastructure are still inadequate, such as incomplete books. Efforts to overcome these obstacles are: increasing apparatus resources in providing understanding to the public about the importance of the Reading Culture Program and providing adequate facilities in terms of book collections, places and locations that are of interest to the community. As well as increasing the quantity and quality of library facilities and infrastructure.